Person‐centred leadership: A relational approach to leadership derived through action research. Issue 15 (23rd July 2018) - Cardiff, Shaun; McCormack, Brendan; McCance, Tanya
Abstract : Aims and objectives: How does person‐centred leadership manifest in clinical nursing. Background: Person‐centred practice fosters healthful relationships and is gaining increasing attention in nursing and health care, but nothing is known about the influence of a person‐centred approach to leadership practice. Most leadership models used in nursing were originally developed outside of nursing. Design: A 3‐year participatory action research study where participant leaders planned, researched and learned from their practice development. Methods: After an orientation phase, four action spirals focused on: critical and creative reflective inquiries into leadership practice change; leading the implementation and evaluation of a new nursing system; facilitating storytelling sessions with staff; and annually reflecting on personal leadership change. Multiple data gathering methods offered insight into leadership development from several perspectives. Results: Critical and creative thematic data analysis revealed a set of attributes, relational processes and contextual factors that influenced the being and becoming of a person‐centred leader. Comparing the findings with nursing leadership literature supports a conceptual framework for person‐centred leadership. Conclusions: Person‐centred leadership is a complex, dynamic, relational and contextualised practice that aims to enable associates and leaders achieve self‐actualisation, empowerment and well‐being. Relevance to clinical practice: This study and its conceptual framework is of relevance to practitioners, educationalists and researchers interested in developing a relational approach to nurse leadership and person‐centred cultures.